Auxiliary alternation in Italian dialects : the project of a database - Fabio Ripamonti; Pavel Štichauer (Études romanes de Brno)
This paper describes the research project named MIXPAR, standing for "MIXed PARadigms", which was previously introduced in Štichauer (2022). The project aims to compile and investigate all published data to date about the phenomenon of mixed perfective auxiliation systems in Italo-Romance. The MIXPAR project represents a database developed following standardized principles currently implemented in a series of morphological lexicons. The article first explains the basic nature of these mixed paradigms, widely attested in a range of Italian dialects, where an intraparadigmatic alternation of two auxiliaries, avere/essere ('have/be'), is found, along with free variation and merged auxiliary forms such as jera, eva, and seva. The paper then introduces the individual parameters of the database, justifying their existence and discussing some of the associated issues. A long-format version of the database is presented, including variables for Cell, Verb/Construction, Class, Tense-aspect-mood paradigm, Auxiliary, Phonosyntactic doubling, Geographical information, Dialectal classification, Source, and Notes. It is concluded that the database will undoubtedly become a valuable tool despite the minor problems that will be resolved in due course.